Some existence results for a class of parabolic equations with nonlinear boundary conditions - LAMAIZI, Anass; EL AHMADI, Mahmoud; BARGHOUTHE, Mohammed; DARHOUCHE, Omar (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
Using the Galerkin approximation and a family of potential wells, we establish the existence of a global weak solution under appropriate conditions. Additionally, we provide a result on the blow-up and asymptotic behavior of certain solutions with positive initial energy. Mathematics Subject Classification (2010): 35A01, 35K05, 35K55. Received 22 March 2025; Accepted 20 July 2025.